Mengenal Pengadilan Tata Usaha Negara Untuk Mewujudkan Pemerintahan Yang Baik (selayar pandang PTUN): State Administrative Court, Policy, Authority - Melani Safitri; Arif Wibowo (Jurnal Penelitian Multidisiplin, 2023)
The rule of law requires that every action or action taken by public authorities or the government has a clear law or legality based on both written and unwritten laws. The government must be neutral and impartial, before all groups in society, and serve the public interest. But in practice, the terms "in the public interest", "development of the whole society", "the state must not harm its citizens" and similar phrases appear repeatedly. political statements by state officials or high-ranking officials, used as a justification for using state power to force a person or group of citizens to comply with the wishes of the government. In order to realize a just and prosperous national and state life order, the government must have a legal system to resolve disputes within society and between the people themselves, the people and the government and government agencies. The State Administrative Court is one of the courts formed by the government to resolve state administrative disputes. The State Administrative Court has the role of adjudicating or settling disputes between the State or State Administration in the State Administrative Court of State Administrative Court officials which was ratified in 1986 by Law Number 51 of 2009 which states that State Administration is a State Administration which has roles and duties in resolving state administrative issues both at the central and regional levels, receiving, investigating, adjudicating and resolving state administrative disputes, so that PTUN has new competencies or tasks in resolving disputes, namely. disputes, diverted in the general election procedure. The problems in this study are First, what are the roles and responsibilities of the State Administrative Court (PTUN) in resolving election disputes in PTUN procedural law? Second, what is the view of siyasa qadhaiyyah regarding the role and function of the State Administrative Court in resolving election disputes? The purpose of this study is to determine the role and duties of the State Administrative Court (PTUN) in resolving election disputes from a procedural viewpoint of the State Administrative Court and to study the opinions of the siyasa qadhaiyyah regarding these roles and tasks. . from the government. to the state administrative court in the settlement of election disputes. The type of research used in this research is field research using various literature, the data analysis method used in this research is data analysis using qualitative inductive and deductive reasoning methods. Based on the research results, researchers can draw the following conclusions: First, the role and function of constitutional law in resolving disputes or differences of opinion in the election process is relatively the same as state administrative disputes in general, namely. investigate, adjudicate and resolve state administrative disputes through individual, final and binding decisions whose decisions are made. have civil consequences. Second, the views of siyasa qadhaiyyah (judiciary) on the role and function of the Administrative Court in resolving election disputes come to monitor/control the authorities and investigate the tyranny of the rulers against their people, including election procedural policies that can harm the people or the people. voters and administrative courts as well as their decisions will commit crimes, and there is no tyranny over people's rights.